2009
DOI: 10.1200/jco.2008.20.2960
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative Hematopoietic Cell Transplantation for Acute Lymphoblastic Leukemia: Analysis of Graft Sources and Long-Term Outcome

Abstract: A B S T R A C T PurposeAnalysis of hematopoietic cell transplantation (HCT) for high-risk or recurrent acute lymphoblastic leukemia (ALL) using different donor sources is confounded by variable conditioning and supportive care. Patients and MethodsWe studied 623 consecutive ALL myeloablative HCT (1980HCT ( to 2005. Donors were autologous (n ϭ 209), related (RD; n ϭ 245), unrelated (URD; n ϭ 100), and umbilical cord blood (UCB; n ϭ 69). ResultsAfter median of 8.3 years of follow-up, 5-year overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 28 publications
3
49
0
1
Order By: Relevance
“…23 In this report, B40% of patients were over 35 years (median age, 33 years; range, 16-59 years). In accordance with other studies, 20,34 our data also showed that older age was associated with higher NRM and lower survival. Thus, the relevance of age factor with regard to transplantation outcomes should be considered.…”
supporting
confidence: 82%
“…23 In this report, B40% of patients were over 35 years (median age, 33 years; range, 16-59 years). In accordance with other studies, 20,34 our data also showed that older age was associated with higher NRM and lower survival. Thus, the relevance of age factor with regard to transplantation outcomes should be considered.…”
supporting
confidence: 82%
“…18 Previous studies had already demonstrated that results after related and unrelated allo-HSCT for adults with ALL were similar. [19][20][21] Allo-SCT from related or matched unrelated donors results in 5-year OS from 40-50% in high-risk patients. Autologous HSCT may be considered in patients lacking a donor, with similar results but higher relapse incidence.…”
Section: Discussionmentioning
confidence: 99%
“…1 Results using alternative stem cell sources or alternative donors have improved in the last decade, and current outcomes after HSCT are strongly correlated with clinical disease status. [2][3][4][5] The optimal results in both children and adults are obtained when patients underwent HSCT at early stages of the disease as measured by conventional morphological remission. [5][6][7] Over the last decade, the concept of remission in ALL has evolved owing to use of molecular techniques and multiparameter flow cytometry (MFC) to more precisely track residual leukemic cells during chemotherapy treatment.…”
Section: Introductionmentioning
confidence: 99%